Synthesis of 10-O-aryl-substituted berberine derivatives by Chan–Evans–Lam coupling and investigation of their DNA-binding properties - Wickhorst, Peter Jonas (Beilstein J Org Chem, 2021)
Eleven novel 10-O-aryl-substituted berberrubine and berberine derivatives were synthesized by the Cu(2+)-catalyzed Chan–Evans–Lam coupling of berberrubine with arylboronic acids and subsequent 9-O-methylation. The reaction is likely introduced by the Cu(2+)-induced demethylation of berberrubine and subsequent arylation of the resulting 10-oxyanion functionality. Thus, this synthetic route represents the first successful Cu-mediated coupling reaction of berberine substrates. The DNA-binding properties of the 10-O-arylberberine derivatives with duplex and quadruplex DNA were studied by thermal DNA denaturation experiments, spectrometric titrations as well as CD and LD spectroscopy. Fluorimetric DNA melting analysis with different types of quadruplex DNA revealed a moderate stabilization of the telomeric quadruplex-forming oligonucleotide sequence G(3)(TTAG(3))(3). The derivatives showed a moderate affinity towards quadruplex DNA (K(b) = 5–9 × 10(5) M(−1)) and ct DNA (K(b) = 3–5 × 10(4) M(−1)) and exhibited a fluorescence light-up effect upon complexation to both DNA forms, with slightly higher intensity in the presence of the quadruplex DNA. Furthermore, the CD- and LD-spectroscopic studies revealed that the title compounds intercalate into ct DNA and bind to G4-DNA by terminal stacking.